Determination of the Relative Configuration of Terminal and Spiroepoxides by Computational Methods: Advantages of the Inclusion of Unscaled Data - Zanardi, Maria Marta (2017)
The assignment of the relative configuration of spiroepoxides or related quaternary carbon-containing oxiranes can be troublesome and difficult to achieve. The use of GIAO NMR shift calculations can provide helpful assistance in challenging cases of structural elucidation. In this regard, the DP4 probability is one of the most popular methods to be employed when only one set of experimental data is available, though modest results were obtained when dealing with spiroepoxides. Recently, we introduced an improved probability (DP4+) that includes the use of both scaled and unscaled NMR data computed at higher levels of theory. Here, we report a comprehensive study to explore the scope and limitations of the DP4+ methodology in the stereoassignment of terminal or spiroepoxides bearing a wide variety of molecular complexity and conformational freedom. The excellent levels of correct classification achieved were interpreted on the basis of a constructive compensation of errors upon using both scaled and unscaled proton and carbon data. The advantages of the DP4+ methodology in solving two case studies that could not be unequivocally assigned by NOE experiments are also provided.